The Leadership of the Head Madrasah Based Quality - wahyudi wahyudi; DYP Sugiharto; Masrukhi Masrukhi; Ahmad Rifai Rc (FITK UIN Walisongo, 2018)
The research focus is to discuss about a leadership of the head madrasah-based quality in Madrasah Aliyah Al Mukmin Muhammadiyah, Tembarak, Temanggung, Central Java. It was used qualitative research. The result shown that the head of the madrasah had a strong desire to realize the vision and mission of the madrasah. He strongly built the quality culture of madrasah based on five principles. There are (1). always being a mukmin and Muslim everywhere and anytime. (2). always friendly in service. (3). having a high professionalism in carrying out administrative duties and adoring the work. (4). creative, dynamic, and innovative in scientific development, and (5). Behave and trustworthy manner, akhlaqul karimah and be role model to other academic community.Abstrak Fokus penelitian adalah untuk membahas tentang kualitas kepemimpinan kepala madrasah di Madrasah Aliyah Al Mukmin Muhammadiyah, Tembarak, Temanggung, Jawa Tengah. Metode penelitian menggunakan penelitian kualitatif. Hasilnya menunjukkan bahwa kepala madrasah memiliki keinginan yang kuat untuk mewujudkan visi dan misi madrasah. Dia sangat membangun budaya kualitas madrasah berdasarkan lima prinsip. (1). selalu menjadi seorang mukmin dan Muslim di mana saja dan kapan saja. (2). selalu ramah dalam pelayanan. (3). memiliki profesionalisme yang tinggi dalam menjalankan tugas-tugas administrasi dan mengagumi pekerjaan. (4). kreatif, dinamis, dan inovatif dalam pengembangan keilmuan, dan (5). berperilaku dan dapat dipercaya, akhlaqul karimah dan menjadi teladan bagi komunitas akademis lainnya.